2015
DOI: 10.1136/oemed-2014-102227
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between low-level benzene exposure and blood cell counts in Korean workers

Abstract: improving information regarding to the work-related diseases and, more specifically, on the trend and variation of benefits paid for them. Method Through the NTEP it is possible to establish a nexus for each area of the economic activity, focusing on data of incapacitating diseases recognised by social welfare and involving more than 15 days' absence from work, using the ICD-10. Results Benefits for work-related diseases increased 128.2% during [2005][2006][2007][2008]. However, the greatest changes occurred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 26 publications
1
36
0
2
Order By: Relevance
“…More recently, Koh et al . used the Korean Special Health Examination Database to assign exposure levels to benzene-exposed workers using process, factory, and industry codes (Koh et al 2015); the authors reported decreased RBCs among male workers exposed to 0.01–0.1 ppm and 0.1–0.5 ppm, compared to the referent group (<0.01 ppm). Three industry-supported occupational studies by Swaen et al , Collins et al ., and Tsai et al ., however, did not report such effects among workers exposed to benzene at air concentrations below one ppm (Collins et al 1991; Swaen et al 2010; Tsai et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Koh et al . used the Korean Special Health Examination Database to assign exposure levels to benzene-exposed workers using process, factory, and industry codes (Koh et al 2015); the authors reported decreased RBCs among male workers exposed to 0.01–0.1 ppm and 0.1–0.5 ppm, compared to the referent group (<0.01 ppm). Three industry-supported occupational studies by Swaen et al , Collins et al ., and Tsai et al ., however, did not report such effects among workers exposed to benzene at air concentrations below one ppm (Collins et al 1991; Swaen et al 2010; Tsai et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our blood VOC concentrations were measured by the laboratory that conducts all NHANES VOC analyses. Our outcomes, the hematologic parameters represented by CBCs and measured in a CLIA-certified laboratory, have been associated with hematologic effects of BTEXS exposures in occupational settings, including at low doses (Koh et al 2015; Lan et al 2004; Qu et al 2002), and have also been used in a few environmental studies (Jeng et al 2006; Lee et al 2002; Pelallo-Martinez et al 2014). Additionally, relevant interview data enabled us to adjust for a range of potential confounding factors and also assess confounding by tobacco smoke exposure, a particularly important confounding variable, in multiple ways, including self-report of primary and passive smoking status in conjunction with a biomarker of tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mandatory limit is being used to this day. Nevertheless, several lines of evidence suggest that BTEX can still be found mainly at low concentrations below the standard levels in many workplaces, whether in developed countries or in developing countries [7,8,9,10,11]. Hence, the influence of long-term exposure to low levels of BTEX on human health effects has become an area of considerable research interest.…”
Section: Introductionmentioning
confidence: 99%
“…Even the smaller body weight, less of inhalation, but longer exposure time, BTEX intake of toddlers were believed to be greater than other studied group. Thus, the hazard health risk for this group is thought to be greater.It has been reported thatlong time exposure of toddlers and children to benzene increases the risk childhood leukemia [1], chronic exposure to benzene is associated with decrease in hemoglobin (Hb), platelet count and while blood cell count [15]. Chronic exposure to xylene has been associated with subjective findings of depression, fatigue, headache, and sleep disrobers [1].…”
Section: Health Risk Assessmentmentioning
confidence: 99%